Exploring the effect of inclusive leadership on psychological distress through organizational climate mediation and moderation - Ibnis Shaid Bin Abdul Rajun; Soon Singh Bikar Singh; Muhamad Suhaimi Taat; Musirin Bin Mosin (Humanities and Social Sciences Letters, 2024)
A new leadership approach called inclusive leadership has emerged in response to today's crises and disasters used by different organizations. Therefore, this study was conducted to identify the effectiveness of inclusive leadership and organizational climate in reducing the widespread prevalence of this symptom among 423 secondary school teachers. Field research data collection was manually analysed using the International Business Machine-Statistical Package for Social Sciences (IBM-SPSS) with moment structure (AMOS) analysis and Jamovi software. The results of the inclusive leadership study are significantly related to organizational climate. The organizational climate is significantly and inversely related to psychological distress. The relationship between inclusive leadership and psychological distress was found to be positive but not significant. Nevertheless, organizational climate fully mediates the relationship between inclusive leadership and psychological distress. However, organizational climate has partially moderated the relationship between inclusive leadership and psychological distress. The study is beneficial to organizational leaders especially the ministry of education and school principals who face diverse secondary school teachers. Finally, it contributes to the development of leadership, management and psychology.